Supracricoid Partial Laryngectomy: Oncological and Functional Outcomes - Mesolella, Massimo; Iorio, Brigida; Buono, Sarah; Cimmino, Mariano; Motta, Gaetano (International Archives of Otorhinolaryngology, 2021)
Introduction In the present study, we have reviewed the outcomes of patients with supracricoid partial laryngectomy (SCPL) in our institution. Our results show that SCPL is a well-tolerated procedure with generally good functional outcomes for patients with advanced laryngeal cancer.Objective We analyzed the oncological and functional results of a cohort of 35 patients who had undergone SCPL, and we highlighted the complications, identified the overall and disease-free survivals, demonstrating that the reconstructive laryngectomy guarantees the oncological safety and reproducibility of the oncological results, preserving the laryngeal functions and promoting an improvement in the patient's quality of life, favoring communication and interpersonal relationships.Methods Between 2010 and 2018, 35 patients underwent SCPL for primary and recurrent laryngeal squamous cell carcinomas, and they were divided into two subgroups: in 16 cases, the cricohyoidoepiglottopexy according to the Mayer-Piquet technique was performed, while the remaining 19 cases were submitted to the cricohyoidopexy according to the Labayle technique. In addition to evaluating the oncological results of patients undergoing reconstructive laryngectomy, the present study also aimed to evaluate the functionality of the residual larynx and the quality of life.Results The overall and disease-free survivals were of 83% and 76.3% respectively. All patients were able to swallow. The nasogastric tube was removed after a mean period of 21.8 days (range: 14 to 28 days). The mean decannulation time was of 23.4 days after surgery (range: 15 to 36 days).Conclusion The curves for the overall and disease-free survivals show that SCPL can guarantee oncological safety comparable to that of total laryngectomies in diseases in the intermediate stage and in carefully-selected advanced stages.
Keywords: Partial Laryngectomy; swallowing disorders; laryngeal cancer; voice